PROBLEMATIKA UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP TINDAK PIDANA MENYERANG KEHORMATAN DAN NAMA BAIK DIKAITKAN DENGAN KEPASTIAN HUKUM - Devi Arviani Arinta; Deny Guntara; Muhamad Abas; Arisa Wongchai (Faculty of Law, Universitas Pekalongan, 2025)
Defamation through electronic media has become an increasingly complex issue amid the rapid development of information technology. Social media facilitates information dissemination but also opens opportunities for the misuse of freedom of expression that may harm others. Article 27A of Law Number 1 of 2024 on Electronic Information and Transactions (EIT Law) has sparked debate due to its ambiguous wording and potential misuse to suppress legitimate criticism. This research employs a normative juridical method by analyzing relevant legislation, legal doctrines, and court decisions. Secondary data were obtained through literature studies and qualitatively analyzed to assess the legal certainty and compatibility of Article 27A with human rights principles, particularly freedom of expression. The findings indicate that Article 27A of the EIT Law remains weak both in its drafting and implementation, especially regarding the phrase